Q_a 1

#$&*

course MTH 279

I was confused on how this one needed to be turned in, seemed as if you wanted this set of notes as an assignment per instructions on the assignment page I may be wrong.

The **** mark and the #$&* mark should each appear by itself, on its own line.We show the following:

• y ' + t y = 0 has solution y = e^(-t^2 / 2).

If y = e^(-t^2 / 2) then y ' = -t e^(-t^2 / 2) so that

y ' + t y becomes -t e^(-t^2 / 2) + t e^(-t^2 / 2), which is zero.

• y ' + sin(t) y = 0 has solution y = e^(cos t)

If y = e^(cos t) then y ' = -sin(t) e^(cos(t)) so that

y ' + t y becomes -sin(t) e^(cos(t)) + sin(t) e^cos(t) = 0

• y ' + t^2 y = 0 has solution y = e^(-t^3 / 3)

This is left to you.

So that y ' + t^2 y becomes -t*e^(-t^3/3) + t^2*(e^(-t^3/3) = 0

#$&*

What do all three solutions have in common?

Some of this is left to you.

However for one thing, note that they all involve the fact that the derivative of a function of form e^(-p(t)) is equal to -p'(t) e^(-p(t)).

And all of these equations are of the form y ' + p(t) y = 0.

Now you are asked to explain the connection.

All of these solutions come from first order linear differential equations that are homogeneous. This means that y ' + p(t) y is equal to zero

#$&*

What would be a solution to each of the following:

• y ' - sqrt(t) y = 0?

If we integrate sqrt(t) we get 2/3 t^(3/2).

The derivative of e^( 2/3 t^(3/2) ) is t^(1/2) e^ ( 2/3 t^(3/2) ), or sqrt(t) e^( 2/3 t^(3/2) ).

Now, if we substitute y = sqrt(t) e^( 2/3 t^(3/2) ) into the equation, do we get a solution? If not, how can we modify our y function to obtain a solution?

We do not get a solution:

Substituting we get = (t) e^( 2/3 t^(3/2) ) - sqrt (t) * sqrt(t) e^( 2/3 t^(3/2) ) = 0

0=0

We could make it separable differential equation setting the y’s on one side and the t’s on the other. We will get the right solution if we use y = e^(2/3 t^3/2

#$&*

• sqrt(t) y ' + y = 0?

The rest of our equations started with y ' . This one starts with sqrt(t) y '.

We can make it like the others if we divide both sides by sqrt(t).

We get

• y ' + 1/sqrt(t) * y = 0.

Follow the process we used before.

We first integrated something. What was it we integrated?

Integrated one side with the y by dy and one with the t with respect to dt

#$&*

We then formed an exponential function, based on our integral. That was our y function. What y function do we get if we imitate the previous problem?

The integral of 1/sqrt(t) is 2sqrt(t) so our y would be e^(2sqrt(t))

#$&*

What do we get if we plug our y function into the equation? Do we get a solution? If not, how can we modify our y function to obtain a solution?

If we use y = e^(2sqrt(t)), y’ = 1/sqrt(t) e^(2sqrt(t)) and plugging into the equation we get 1/sqrt(t) e^(2sqrt(t)) - 1/sqrt(t) e^(2sqrt(t)) which is equal to zero

#$&*

• t y ' = y?

If we divide both sides by t and subtract the right-hand side from both sides what equation do we get?

y’ - y/t = 0

#$&*

Why would we want to have done this?

To put the equation in a more workable form based on what we have already done.

#$&*

Imitating the reasoning we have seen, what is our y function?

e^ (ln(t)) = t

#$&*

Does it work?

y = t, y’= 1 so plugging in we get 1- (1/ t) (t) =0

1-1 = 0

It works

#$&*

• y ' + p(t) y = 0 has solution y = e^(- int(p(t) dt)).

This says that you integrate the p(t) function and use it to form your solution y = e^(- int(p(t) dt)).

Does this encapsulate the method we have been using?

Yes, if I am understanding it correctly

#$&*

Will it always work?

yes

#$&*

What do you get if you plug y = e^(-int(p(t) dt) into the equation y ' + p(t) y = 0?

- int(e^(-int(p(t))dt)) + p(t) e^(-int(p(t) dt) = 0

#$&*

Is the equation satisfied?

Yes the equation is satisfied

#$&*

y ' + p(t) y = 0 is the general form of what we call a first-order linear homogeneous equation. If it can be put into this form, then it is a first-order linear homogeneous equation.

Which of the following is a homogeneous first-order linear equation?

• y * y ' + sin(t) y = 0

We need y ' to have coefficient 1. We get that if we divide both sides by y.

Having done this, is our equation in the form y ' + p(t) y = 0?

No because if one divides by “y” then y is cancelled in the second part of the equation

#$&*

Is our equation therefore a homogeneous first-order linear equation?

No this is not

#$&*

• t * y ' + t^2 y = 0

Once more, we need y ' to have coefficient 1.

What is your conclusion?

Yes this is a first order linear homogenous equation

#$&*

• cos(t) y ' = - sin(t) y

Again you need y ' to have coefficient 1.

Then you need the right-hand side to be 0.

Put the equation into this form, then see what you think.

y’ + tan(t) y

it is a first order linear differential equation

#$&*

• y ' + t y^2 = 0

What do you think?

This is not linear, but it is a first order homogenous equation

#$&*

• y ' + y = t

How about this one?

This is is linear first order equation but not a homogenous equation because there is an additional -t on the left side

#$&*

Solve the equations above that are homogeneous first-order linear equations.

1. t * y ' + t^2 y = 0

y’ + ty = 0

y = e^(t^2/2)

y’ = t e^(t^2/2)

t e^(t^2/2) + t e^(t^2/2) = 0

2. cos(t) y ' = - sin(t) y

y’ + tan(t) y = 0

y = e^(-ln(cos(t)))

y’ = -tan ( e^ (-ln(cos(t))))

-tan ( e^ (-ln(cos(t)))) + tan(t) e^(-ln(cos(t)))

#$&*

Verify the following:

• If you multiply both sides of the equation y ' + t y by e^(t^2 / 2), the result is the derivative with respect to t of e^(t^2 / 2) * y.

The derivative with respect to t of e^(t^2 / 2) * y is easily found by the product rule to be

(e^(t^2 / 2) * y) '

= (e ^ (t^2 / 2) ) ' y + e^(t^2/2) * y '

= t e^(t^2/2) * y + e^(t^2 / 2) * y '.

If you multiply both sides of y ' + t y by e^(t^2 / 2) you get e^(t^2 / 2) y ' + t e^(t^2 / 2).

Same thing.

Now, what is it in the original expression y ' + t y that led us to come up with t^2 / 2 to put into that exponent?

y’ + ty

#$&*

• If you multiply the expression y ' + cos(t) y by e^(sin(t) ), the result is the derivative with respect to t of e^(-sin(t)) * y.

Just do what it says. Find the t derivative of e^(sin(t) ) * y. Then multiply both sides of the expression y ' + cos(t) y by e^(sin(t) * y).

The derivative of e^(sin(t))*y is e^(sin(t))*y’ + cos(t) e^(sin(t))*y

Which is the same as if you multiplied e^(sin(t))*y by y’ + cos(t).

#$&*

How did we get e^(sin(t)) from of the expression y ' + cos(t) y? Where did that sin(t) come from?

When we took the integral of t we found it was equal to sin(t)

#$&*

• If you multiply both sides of the equation y ' + t y = t by e^(t^2 / 2), the integral with respect to t of the left-hand side will be e^(t^2 / 2) * y.

You should have the pattern by now. What do you get, and how did we get t^2 / 2 from the expression y ' + t y = t in the first place?

The answer is given below so I was uncertain if I needed to answer with the same answer.

#$&*

The equation becomes e^(t^2 / 2) * y ' + t e^(t^2 / 2) y = t e^(t^2 / 2).

The left-hand side, as we can easily see, is the derivative with respect to t of e^(t^2 / 2) * y.

So if we integrate the left-hand side with respect to t, since the left-hand side is the derivative of e^(t^2 / 2) * y, an antiderivative is e^(t^2 / 2) * y.

Explain why it's so.

It is so because if one were to integrate t, then one would raise the power divide by the new power and in a first order linear equation, it is of the form e^ (-int(t))

#$&*

Having integrated the left-hand side, we integrate the right-hand side t e^(t^2 / 2).

What do you get? Be sure to include an integration constant.

e^(t^2/2) + C

#$&*

Set the results of the two integrations equal and solve for y. What is your result?

e^( t^2/2) *y = e^(t^2/2) + C divide each side to isolate y

y = 1 + C/e^( t^2/2)

#$&*

Is it a solution to the original equation?

y ' = -c t e^(-t^2 / 2)

so yes it is the identity

#$&*

• If you multiply both sides of the equation y ' + p(t) y = g(t) by the e raised to the t integral of p(t), the left-hand side becomes the derivative with respect to t of e^(integral(p(t) dt) ) * y.

See if you can prove this.

The integral of 2t is t^2 so we will multiply e^(t^2) by both sides of the equation

y’ + 2t*y = 4t

e^(t^2)*y’ + 2t e^(t^2)*y = 4t e^(t^2)

The left hand side of the equation turns out to be the derivative with respect to t of e^(t^2) * y

#$&*

"

&#This looks good. Let me know if you have any questions. &#